2018
DOI: 10.1161/jaha.117.007824
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Lipoprotein Subspecies Defined by Apolipoprotein C‐III and Subclinical Atherosclerosis Measures: MESA (The Multi‐Ethnic Study of Atherosclerosis)

Abstract: BackgroundApolipoprotein C‐III (apoC‐III), a small proinflammatory protein present on 6% to 7% of high‐density lipoprotein (HDL) particles, defines a subspecies of HDL adversely associated with coronary heart disease in primarily white cohorts. In a multi‐ethnic population free of clinical cardiovascular disease, we evaluated the relationship between apoC‐III–defined HDL subspecies and subclinical markers of atherosclerotic pathology.Methods and ResultsWe investigated cross‐sectional associations between apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
5
14
0
Order By: Relevance
“…The current results and our prior findings [15,18,38] indicate that, beyond its inherent atherogenic and diabetogenic properties, apoC-III may be involved in cardiometabolic disease processes as a modulator of HDL function. We previously reported that only HDL lacking apoC-III was inversely associated with risk of coronary heart disease in four cohorts [38] and with cross-sectional measures of subclinical atherosclerosis in MESA [18], and thus HDL containing apoC-III may constitute a dysfunctional subspecies of HDL lacking cardioprotective potential. Little is currently known about the functional involvement of these apoC-III-defined HDL subspecies in the development of diabetes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The current results and our prior findings [15,18,38] indicate that, beyond its inherent atherogenic and diabetogenic properties, apoC-III may be involved in cardiometabolic disease processes as a modulator of HDL function. We previously reported that only HDL lacking apoC-III was inversely associated with risk of coronary heart disease in four cohorts [38] and with cross-sectional measures of subclinical atherosclerosis in MESA [18], and thus HDL containing apoC-III may constitute a dysfunctional subspecies of HDL lacking cardioprotective potential. Little is currently known about the functional involvement of these apoC-III-defined HDL subspecies in the development of diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to its direct role in cardiometabolic disease pathophysiology, apoC-III may modify the functions of the lipoproteins on which it resides. We previously demonstrated in several cohorts that the presence of apoC-III diminishes the established inverse association of HDL with CHD [17] and subclinical atherosclerosis [18] and strengthens the positive association of LDL with risk of CHD [19], suggesting that apoC-III may disrupt the cardioprotective functions of HDL and enhance the atherogenicity of LDL. Our findings for cardiovascular outcomes led us to hypothesise that apoC-III may similarly counter the emerging anti-diabetogenic properties of HDL, which include the regulation of glucose and insulin secretion and the suppression of inflammation in metabolic tissues [2].…”
Section: Introductionmentioning
confidence: 94%
“…When carotid intima-media thickness was measured cross-sectionally and prospectively in subjects with T1D, it pointed to an adverse association to apoCIII [ 104 ]. Data from humans reveal that HDL containing apoCIII no longer acts as the “good protective cholesterol”, but instead is related to an increased risk of atherogenesis and diabetes, which further confirms the complexity of this apolipoprotein [ 105 , 106 ].…”
Section: Discussionmentioning
confidence: 87%
“…In our study, we observed the risk to increase by approximately 10% for every mg/dl increase in total APOC3 for "any CVD" event and for MACEs. In a recent report of 4,659 participants with CVD risk factors in the Multi-Ethnic Study of Atherosclerosis, HDL particles containing APOC3 were positively associated with coronary artery calcification in women (41). Our findings are consistent with these previous observations, as we observed nominally significant positive associations of the HDL-containing subfraction of APOC3 (APOC3-HS) with "any CVD" event and with MACEs: this persisted in our most rigorously adjusted model, which adjusted for SBP and pulse, both prespecified variables in our analytic plan.…”
Section: Discussionmentioning
confidence: 97%